Has EU Accession Caused Structural Change in New Entrants? Intersectoral Linkage Analyses on Bulgaria and Romania - Demiral, Mehmet (International Journal of Economics and Financial Issues, 2016)
The European Union (EU) countries, especially the founders and earlier entrants (EU-15) are among the most-developed, post-industrial and innovation-driven economies in the world. Countries with different structures are expected to have progressive structural changes after their accessions to the EU by means of the intra-EU policies on socio-economic integration and monetary (euro) adoption. Starting from this convergence premise, this study aims to explore whether the latest member states, Bulgaria and Romania, that joined the EU in 2007, have experienced significant changes in their economic structures. To this end, with a general equilibrium approach and using input-output data of the countries, we conduct intersectoral linkage analyses covering all economic activities aggregated to 34 sectors for the years of 1995, 2002, 2007 and 2011. Backward and forward linkage coefficients calculated from inverse matrices based on the Leontief model and the Ghosh model reveal that there is no strong evidence found supporting the structural changes experiences in the fifth year of the EU accession for both countries.